Genome-Wide Comparative Analysis of Heat Shock Transcription Factors Provides Novel Insights for Evolutionary History and Expression Characterization in Cotton Diploid and Tetraploid Genomes - Liang, Yajun; Wang, Junduo; Zheng, Juyun; Gong, Zhaolong; Li, Zhiqiang; Ai, Xiantao; Li, Xueyuan; Chen, Quanjia (Frontiers in Genetics, 2021)
Heat shock transcription factors (HSFs) involved in environmental stress response and plant development, such as heat stress and flowering development. According to the structural characteristics of HSF gene family, HSF genes were classified into three major types (HSFA, HSFB, and HSFC) in plants. Using conserved domains of HSF genes, we identified 621 HSF genes among 13 cotton genomes, including eight diploid and five tetraploid genomes. Phylogenetic analysis indicated that HSF genes among 13 cotton genomes were grouped into two different clusters, and one cluster contained all HSF genes of HSFA and HSFC, with another cluster containing all HSF genes of HSFB. Comparative analysis of HSF genes in Arabidopsis thaliana, Gossypium herbaceum (A1), Gossypium arboretum (A2), Gossypium raimondii (D5) and Gossypium hirsutum (AD1) genomes demonstrated that four HSF genes were inherited from the common ancestor, A0, of all existing cotton A genomes. The members of HSF gene family in G. herbaceum (A1) genome indicated significant loss compared with these in G. arboretum (A2) and Gossypium hirsutum (AD1) A genomes. Except that, HSF genes in G. raimondii (D5) showed relative loss compared with these in G. hirsutum (AD1) D genome. Analysis of tandem duplication (TD) events of HSF genes revealed that protein-coding genes among different cotton genomes have experienced tandem duplication events, but only two-gene tandem array was detected in Gossypium thurberi (D1) genome. The expression analysis of HSF genes in G. hirsutum (AD1) and G. barbadense (AD2) genomes indicated the expressed HSF genes were divided into two different groups respectively and the expressed HSF orthologous genes between the two genomes showed totally different expression patterns although the implementation of same abiotic stresses. This work will provide novel insights for the study of evolutionary history and expression characterization of HSF genes in different cottons genomes and widespread application model for the study of HSF gene families in plants.